Optimasi Biaya Distribusi Multi-eselon untuk Multi-produk Menggunakan Mix Integer Linier Programming - Erika Fatma; Supardi Manurung (Institut Transportasi dan Logistik Trisakti, 2021)
The transportation problem is one of the fundamental problems in distribution network to minimize transportation costs by considering resource constraints and meeting the customer demand. This study aims to minimize distribution costs of a distribution networks of soft drink company using the Mix Integer Linear Programming (MILP). This optimization method considers transportation costs, material handling and transportation costs. The addition of a distribution center (DC) as a consolidation center of goods sent to retailers makes the distribution process more efficient. Facility and material handling costs in DC, can be compensated with lower transportation costs. The suggested network can reduce distribution costs by 15.29% compared to the existing methods.